Analisis Framing Pemberitaan Otorita IKN Pada Media Lokal Kalimantan Timur Mediakaltim.Com dan Kaltimpost.Jawapos.Com - Adams, Aburizal; Mayasari, Mayasari; Wahyu Utamidewi (CV. ULIL ALBAB CORP, 2025)
This study discusses the analysis of the news framing of the Indonesian Capital Authority (IKN) by two local media in East Kalimantan, namely Mediakaltim.com and Kaltimpost.jawapos.com. This study uses a qualitative descriptive method with the Pan and Kosicki framing analysis model approach which includes four structures: syntax, script, thematic, and rhetorical. Data were collected through documentation of ten news items with 5 news items each from each media published on March 1–April 15, 2025. The results of the study show that both media frame the IKN Authority positively, by highlighting narratives of success, clarification of negative issues, and participation in social and environmental programs. However, the framing used tends to be one-way and there is no criticism, comparison or opposing response from the public, experts, or community institutions, with the dominance of quotes from the government or official institutions. This finding shows that there needs to be a balance of information so that the reporting of information is more objective and comprehensive because it can shape public perception.